X-ray computed tomography of two mammoth calf mummies. (July 2014) - Fisher, Daniel C.; Shirley, Ethan A.; Whalen, Christopher D.; Calamari, Zachary T.; Rountrey, Adam N.; Tikhonov, Alexei N.; Buigues, Bernard; Lacombat, Frédéric; Grigoriev, Semyon; Lazarev, Piotr A.
Abstract : Two female woolly mammoth neonates from permafrost in the Siberian Arctic are the most complete mammoth specimens known. Lyuba, found on the Yamal Peninsula, and Khroma, from northernmost Yakutia, died at ages of approximately one and two months, respectively. Both specimens were CT-scanned, yielding detailed information on the stage of development of their dentition and skeleton and insight into conditions associated with death. Both mammoths died after aspirating mud. Khroma's body was frozen soon after death, leaving her tissues in excellent condition, whereas Lyuba's body underwent postmortem changes that resulted in authigenic formation of nodules of the mineral vivianite associated with her cranium and within diaphyses of long bones. CT data provide the only comprehensive approach to mapping vivianite distribution. Three-dimensional modeling and measurement of segmented long bones permits comparison between these individuals and with previously recovered specimens. CT scans of long bones and foot bones show developmental features such as density gradients that reveal ossification centers. The braincase of Khroma was segmented to show the approximate morphology of the brain; its volume is slightly less (∼2, 300 cm 3 ) than that of neonate elephants (∼2, 500 cm 3 ). Lyuba's premaxillae are more gracile than those of Khroma, possibly a result of temporal and/or geographic variation but probably also reflective of their age difference. Segmentation of CT data and 3-D modeling software were used to produce models of teeth that were too complex for traditional molding and casting techniques.